Musculoskeletal health considerations for the transgender athlete - Birnbaum, A.; Karamitopoulos, M.; Carter, C. W. (The Physician and Sportsmedicine, 2023)
Background In addition to the familiar sports-related injuries and conditions experienced by cisgender athletes, transgender athletes may also face unique challenges to maintaining their musculoskeletal health. Encouraging sports medicine professionals to become familiar with accepted nomenclature and terminology related to transgender athletes will enable open communication on the field, in the athletic training facility, and office.